High-air-permeability humidity display film based on optical interference and preparation process thereof
By designing a high-breathable humidity display film with a multi-layer structure and a microporous design in the humidity display film, the problems of slow humidity response speed, poor breathability and insufficient mechanical stability in the prior art are solved, and rapid humidity conduction and gradient display effects are achieved.
Patent Information
- Application Number
- CN202411944859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing humidity display films have shortcomings in humidity response speed, breathability, mechanical stability and gradient humidity display functions, and cannot quickly reflect humidity changes and are prone to water vapor accumulation in high-humidity environments.
A high-permeable humidity display film design based on optical interference, including a transparent base layer, a humidity response layer, an intermediate nanofiber breathable layer and a hydrophobic layer, is adopted to achieve rapid conduction and display of humidity through multi-layer structure and micropore design.
It has achieved an improvement in humidity response speed, high breathability and good mechanical stability, and can maintain stability in a high humidity environment and display a humidity gradient.
Abstract
Description
Technical Field
[0001] The invention relates to a high air permeability humidity display film based on optical interference and a preparation process thereof. Background Art
[0002] Humidity display films are widely used in packaging, smart labels, environmental monitoring and other fields, and can directly reflect changes in environmental humidity through visible color changes. In the prior art, hydrogel films, cellulose nanocrystal films and layer-by-layer self-assembled (LBL) films have been reported.
[0003] However, cellulose nanocrystal films and hydrogel nano-microcavity films rely on the hygroscopic expansion of materials to achieve humidity display, but their expansion speed is limited, resulting in a relatively delayed humidity response, unable to quickly reflect humidity changes, and no gradient humidity display function. Although the humidity-responsive LBL film has a simple process, the layer-by-layer deposition structure increases the humidity conduction path, resulting in a delayed humidity response. Hydrogel nano-microcavity films and cellulose nanocrystal films are prone to brittleness after humidity expansion, and their mechanical stability decreases. They may crack or deform after humidity changes cycle. Although the humidity-responsive LBL film has a layered structure that increases the thickness, the interlayer bonding force is weak, and interlayer separation is prone to occur during long-term use, reducing the durability of the material. In addition, these three technologies do not include breathable design in the selection of materials for the humidity-sensitive layer, which makes it easy for water vapor to accumulate in the material in a high humidity environment, affecting the humidity indication effect and limiting the material's usage scenarios. Summary of the invention
[0004] In order to overcome the above defects, the present invention provides a high air permeability humidity display film based on optical interference and a preparation process thereof.
[0005] To achieve the above-mentioned purpose, the highly breathable humidity display film based on optical interference of the present invention comprises: a base layer, a humidity response layer, an intermediate layer and a hydrophobic layer;
[0006] The base layer is made of transparent material; a plurality of air-permeable micropores are arranged on the base layer; the pore size of the micropores is 1-10 μm; and the porosity is 10-20%;
[0007] The humidity response layer is a thin film layer made of humidity sensitive material with a thickness of 50-100 μm, on which micropores are arranged, and the pore size of the micropores is 0.5-2 μm; to ensure that air and water vapor can freely penetrate the humidity response layer;
[0008] The middle layer is a nanofiber membrane, wherein the fiber diameter of the nanofiber is controlled to be 100-300nm; the density of the middle layer in the length direction changes in a gradient to control the air permeability of the humidity response layer corresponding to the middle layer of different density;
[0009] The hydrophobic layer is made of a transparent and breathable material, providing good protection for the humidity display film.
[0010] Furthermore, the humidity sensitive material is polyethylene glycol or polyvinyl alcohol.
[0011] To achieve the above object, the preparation process of the high air permeability humidity display film based on optical interference of the present invention at least includes the step of preparing the base layer, specifically:
[0012] Use polyester or polycarbonate as the base film with a thickness of 30μm-100μm;
[0013] The base film is processed by laser drilling, the laser power is set to 5-15W, the scanning rate is 10-20μm / s, and micropores with a pore size of 1-10μm and a porosity of 10-20% are prepared;
[0014] The punched base film is treated with oxygen plasma at a gas flow rate of 50-100 sccm, a power of 50-100 W, and a treatment time of 30-60 s to improve the adhesion of the gradient humidity response layer.
[0015] Furthermore, the process also includes the step of preparing the humidity response layer, specifically:
[0016] Prepare a water or ethanol solution of polyethylene glycol or polyvinyl alcohol with a concentration of 5-10wt%;
[0017] The film is formed by spin coating, the spin coating speed is controlled at 1000-1500 rpm, and the time is set to 30-60 s to obtain a film with a thickness of 50-100 μm;
[0018] In the film forming process, polystyrene microspheres are added as templates, the particle size of the microspheres is controlled at 0.5-2 μm, and the doping amount is 10-20 wt%;
[0019] After coating and forming a film, the microsphere template is evaporated to form a microporous structure through a drying treatment at 40-60°C for 1-2 hours.
[0020] Furthermore, the process also includes the step of preparing the intermediate layer, specifically:
[0021] Prepare polyacrylonitrile electrospinning solution, the concentration of which is controlled at 8-12wt% to ensure the fluidity and spinning formability of the solution;
[0022] The area with slow moisture conduction rate was prepared to form a high-density fiber structure, the voltage was set in the range of 20-25 kV, the fiber deposition amount was increased, and the spinning rate was controlled at 1.0 mL / h to generate a dense fiber layer;
[0023] A low-density fiber structure is formed in the area with faster moisture conduction. The voltage is set at 15-20 kV and the spinning rate is lowered to 0.5 mL / h to form a looser fiber layer, allowing moisture to pass through faster.
[0024] After electrospinning, the formed PAN fiber membrane was subjected to low temperature heat treatment at 60-80°C for 1-2h.
[0025] Furthermore, the method further comprises the step of preparing a hydrophobic layer:
[0026] Preparing a PVDF solution with a concentration of 5-10wt%;
[0027] Phase separation in a cold water bath forms a PVDF porous membrane with a porosity of 10-30% and a pore size of 100-500nm;
[0028] Dry at room temperature for 30 min.
[0029] The present invention has the following advantages:
[0030] 1. Fast humidity response speed. The present invention adopts hydrophilic microporous structure material and realizes rapid humidity conduction through multi-layer design. The change of humidity will be quickly transmitted to the humidity response layer, resulting in immediate color change, and the humidity indication effect is more sensitive.
[0031] 2. High air permeability. The base layer and the hydrophilic layer (humidity response layer) of the present invention are both designed with microporous structures, which ensure that water vapor can freely penetrate the film while preventing water vapor from accumulating in the film. This high air permeability prolongs the stability of humidity display and is particularly suitable for application scenarios that require rapid humidity display and high air permeability.
[0032] 3. Good mechanical stability. The multi-layer structure design enables each layer to have specific functions, and the plasma treatment enhances the interlayer bonding force and improves the overall mechanical stability of the film. The film will not crack or deform during the cyclic use of humidity changes, and has a longer service life.
[0033] 4. The humidity display effect is reversible and durable. The present invention realizes color change by changing the optical thickness of the humidity response layer, ensuring that the color effect of humidity display can be repeatedly displayed and restored, and has high stability under humidity changes. DETAILED DESCRIPTION
[0034] In the description of the present invention, it is necessary to understand that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like to indicate directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the present invention.
[0035] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0036] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0037] The present invention aims to design a highly breathable material with humidity display function based on the humidity response differences of different materials. The material consists of a porous structure substrate, a hydrophilic layer (humidity response layer), an intermediate nanofiber breathable layer and a hydrophobic layer. Through the alternating combination of hydrophilic and hydrophobic materials, the material exhibits different expansion or contraction behaviors in a humidity environment, relying on optical interference and optical phase changes to achieve a humidity indication effect.
[0038] Basal layer
[0039] The base layer is made of transparent polyester (PET) or polycarbonate (PC) material with microporous structure, which has high light transmittance and excellent mechanical properties, and is suitable for supporting materials of multi-layer humidity display film structure. The light transmittance of PET and PC is as high as 90% and 85% respectively, ensuring that the color change of humidity display film is clearly visible; both materials have good thermal stability, the glass transition temperature of PET is about 80℃, and PC can reach 150℃, giving them dimensional stability during processing and use. In addition, PET and PC have flat surfaces and good flexibility, which are suitable for making humidity display films that need to be bent or deformed, and provide stable support for subsequent layer structures.
[0040] In order to achieve air permeability, the present invention performs micro-pore processing on PET or PC materials through a laser drilling process to form a porous structure with air permeability. The laser drilling process utilizes precisely controlled laser power and scanning rate to form uniform micro-pores and achieve an effective balance between the air permeability and strength of the material. Using a laser with a power of 5-10W and a scanning rate of 10-20μm / s, micro-pores with a diameter of 1-10μm are processed on the PET or PC substrate, and the porosity is controlled between 10-20%, ensuring that the substrate layer has the required air permeability and structural integrity. The advantage of laser drilling is that it is flexible in operation and is suitable for substrate materials of different thicknesses and sizes. It not only ensures air permeability, but also maintains the uniformity and stability of the overall performance of the film.
[0041] In addition, in order to enhance the adhesion between the hydrophilic layer and the substrate, the present invention performs oxygen plasma treatment on the surface of the substrate after laser drilling. The gas flow rate of the oxygen plasma is set to 50-100sccm, the power is 50-100W, and the treatment time is 30-60s to introduce active functional groups on the substrate surface to enhance its bonding with the hydrophilic layer. The substrate layer after laser microporous processing and plasma treatment has good light transmittance, air permeability and interlayer adhesion, providing a stable basic structure for the realization of the humidity display film.
[0042] Humidity responsive layer
[0043] The humidity responsive layer is also a hydrophilic layer. It uses the principle that when light is reflected and transmitted between different layers in the film, if the optical path difference between the layers satisfies the conditions of constructive interference or destructive interference, light of a specific wavelength is enhanced or weakened, causing the film to present different colors.
[0044] The optical path difference of light in a multilayer film is the key to color formation. The formula for the optical path difference is: Δ = 2 × n × d × cos (θ), where Δ is the optical path difference, n is the refractive index of each layer of material, d is the thickness of each layer of material, and θ is the incident angle of light in the material. For the optical path difference Δ, the condition for constructive interference is: Δ = m × λ, and the condition for destructive interference is: Δ = (m + 1 / 2) × λ, where m is the interference order (integer), and λ is the wavelength of light (the visible light range is usually between 400-700nm). The hydrophilic layer (humidity response layer) of the present invention can be made of polyethylene glycol (PEG) or polyvinyl alcohol (PVA) materials with humidity-sensitive properties. Both can significantly expand and produce refractive index changes in a humidity-changing environment, thereby changing the interference conditions of light of different wavelengths, and producing a color display effect through optical phase changes. The molecular weight of PEG material is controlled at 5000-10000g / mol to ensure its proper solubility and hygroscopicity; the alcoholysis degree of PVA material is 87-89%, which can provide excellent humidity responsiveness and good mechanical strength. Both materials can show good hygroscopic expansion performance in high humidity environment, making the hydrophilic layer sensitive to humidity changes.
[0045] In order to make the hydrophilic layer have both air permeability and humidity response function, the present invention prepares the hydrophilic layer by combining a solution coating process with a microporous structure. The solution coating process is simple and easy, and the hydrophilic polymer can be evenly coated on the substrate in a short time. A uniform film thickness can be formed by controlling the rotation speed and time of spin coating. The concentration of PEG or PVA in water or ethanol solution is controlled at 5-10wt% to ensure that the solution can form a uniform film layer during the film forming process. The film is formed by spin coating, the spin coating speed is controlled at 1000-1500rpm, and the time is set to 30-60s to obtain a film with a thickness of 50-100μm. During the film forming process, a microporous structure is realized by adding polystyrene (PS) microspheres as a template, and a microporous structure with controllable size can be left during the film drying process, so as to achieve the desired micropore pore size and uniform distribution drying. The microsphere template only guides the formation of micropores at the physical level, does not affect the hygroscopic expansion characteristics and mechanical strength of the material, does not produce residues after the microspheres volatilize, and maintains the purity of the hydrophilic layer. The particle size of the microspheres is controlled at 0.5-2 μm, and the doping amount is 10-20 wt %, ensuring that the hydrophilic layer has appropriate air permeability while responding to humidity.
[0046] After coating and forming a film, the microsphere template is dried at 40-60℃ for 1-2h, and the microsphere template evaporates to form a microporous structure, further enhancing the air permeability and humidity response effect of the film. The microporous structure ensures that air and water vapor can freely penetrate the hydrophilic layer to achieve rapid humidity conduction. At the same time, the uniform distribution of micropores ensures the stability of the material structure. The hydrophilic layer after drying has uniform thickness and pore size, and has excellent humidity responsiveness and air permeability. It is the core component to achieve the humidity display effect.
[0047] Middle layer (nanofiber breathable layer)
[0048] The intermediate layer (nanofiber breathable layer) can adopt polyacrylonitrile (PAN) nanofiber membrane with different density gradients, and its main function is to maintain the mechanical stability of the structure and enable the material to have the function of humidity gradient display. Polyacrylonitrile has good mechanical properties and moisture resistance, and the formed nanofiber structure can ensure the free penetration of air and water vapor, while effectively buffering the humidity expansion of the hydrophilic layer. The fiber diameter of PAN nanofiber is controlled in the range of 100-300nm to provide appropriate porosity and air permeability, while maintaining the mechanical strength and overall integrity of the film structure. By adjusting the fiber density by partition, a gradient of humidity conduction is formed in the intermediate layer to meet the gradient response requirements of humidity display.
[0049] The PAN concentration of the electrospinning solution is controlled at 8-12wt% to ensure the fluidity and spinning formability of the solution. In order to form a high-density fiber structure in areas with slower moisture conduction rates, the voltage is set in the range of 20-25kV, the fiber deposition amount is increased, and the spinning rate is controlled at 1.0mL / h to generate a dense fiber layer; while the voltage is set at 15-20kV in areas with faster moisture conduction, and the spinning rate is reduced to 0.5mL / h to form a looser fiber layer, allowing moisture to pass through faster.
[0050] After electrospinning, the formed PAN fiber membrane is heat treated at 60-80℃ for 1-2h to further enhance the bonding strength and structural stability between the fibers. After heat treatment, the fiber diameter and porosity of the middle layer are uniform, and the air permeability and mechanical properties are good, providing key support for the air permeability and durability of the humidity display film.
[0051] Hydrophobic layer (nanoporous protective layer)
[0052] The hydrophobic layer (nanoporous protective layer) can be made of polyvinylidene fluoride (PVDF) or polydimethylsiloxane (PDMS) materials, the purpose of which is to provide good protection for the humidity display film and ensure the stability of the humidity indication function. PVDF and PDMS materials have good hydrophobicity and chemical stability, can prevent water penetration in a humid environment, and provide necessary air permeability through the surface nanoporous structure. The pore size of the porous hydrophobic layer is controlled in the range of 100-500nm, so that water vapor can pass smoothly, while liquid water is difficult to penetrate, effectively protecting the humidity response layer and internal structure.
[0053] The hydrophobic layer is prepared by phase separation to ensure the uniformity of the nanoporous structure. The PVDF solution uses dimethylformamide (DMF) as a solvent and the concentration is controlled at 5-10wt% to form an appropriate membrane thickness and porosity. The solution is phase separated in a cold water bath to form a PVDF porous membrane with a porosity of 10-30%, achieving the required permeability and hydrophobicity.
[0054] If PDMS material is used, its precursor solution is mixed in a ratio of 10:1 and evenly coated on the middle layer to form a nanoporous membrane layer through natural volatilization. After film formation, the PDMS membrane is baked at 80-100℃ for 30-60min to achieve complete curing, and the PVDF membrane is naturally dried at room temperature. The porous structure of the hydrophobic layer membrane surface after curing is uniform, with excellent hydrophobicity and air permeability, while protecting the film structure from the influence of liquid water during humidity changes, ensuring the stability and durability of humidity display.
[0055] The present invention will be further described below in conjunction with embodiments:
[0056] Example 1
[0057] 1. Preparation of substrate layer: Transparent polyethylene terephthalate (PET) was used as the substrate with a thickness of 50 μm. The substrate was processed by laser drilling, with the laser power set to 8W and the scanning rate to 15 μm / s, to prepare a microporous structure with a pore size of 5 μm and a porosity of 15% to enhance air permeability. After oxygen plasma treatment, the gas flow rate was 80 sccm, the power was 80 W, and the treatment time was 45 s to improve the adhesion of the hydrophilic layer (humidity response layer).
[0058] 2. Preparation of hydrophilic layer (humidity responsive layer): Prepare a 7 wt % PVA aqueous solution with a degree of alcoholysis of 88%. Apply the PVA solution on a microporous PET substrate at a spin coating speed of 1200 rpm for 45 s to form a hydrophilic layer (humidity responsive layer) with a thickness of 80 μm.
[0059] Dry at 50°C for 1h to form a microporous structure. Use polystyrene (PS) microspheres with a particle size of 1.5μm as a template with a doping amount of 15wt%. Volatilize during the drying process to form a microporous structure. The final hydrophilic layer (humidity response layer) has a pore size of 1-1.5μm.
[0060] 3. Preparation of the middle layer: Using a 10wt% polyacrylonitrile (PAN) solution, the nanofiber layer was deposited on the hydrophilic layer (humidity response layer) by electrospinning. High-density area: The humidity conduction rate is slow, the voltage is set to 25kV, the spinning rate is 1.0mL / h, the receiving distance is 10cm, and the spinning time is 5min, forming a dense fiber layer. Low-density area: The humidity conduction rate is fast, the voltage is set to 15kV, the spinning rate is 0.5mL / h, the receiving distance is 15cm, and the spinning time is 2min, forming a sparse fiber layer. Heat treatment at 70°C for 1h to increase the interlayer bonding force.
[0061] 4. Preparation of hydrophobic layer: A PVDF solution with a concentration of 8wt% was used to prepare a nanoporous membrane layer using a phase separation method, with a porosity of 20% and a pore size controlled at 300 nanometers. The hydrophobic layer was 20μm thick and dried at room temperature for 30 minutes to ensure water resistance when humidity passes through.
[0062] 5. Test results: Under 30% to 90% relative humidity conditions, the film color change response time is 3-5s. When the humidity increases from 30% to 90%, the film color gradually changes from light blue to yellow, showing a good humidity display effect. The film has no obvious cracking after 200 humidity cycles, indicating good mechanical durability. The refractive indices of the 50μm PET base layer and the 80μm PVA hydrophilic layer were measured to be 1.65 and 1.49 respectively, and the optical path difference Δ=2×(1.65×50+1.49×80)=403.4μm. The color of the film before color development was light blue (λ≈490), and the interference order = 403.4 / 0.49≈823 can be obtained. The thickness of the hydrophilic layer after moisture absorption is 100μm, and the refractive index is 1.53. The optical path difference Δ=2×(1.65×50+1.53×100)=471μm, then the interference wavelength after moisture absorption is λ=471 / 823×1000=572nm, which is the wavelength of yellow light.
[0063] Example 2
[0064] 1. Preparation of substrate layer: Polycarbonate (PC) material was used as the substrate with a thickness of 60 μm and a light transmittance of 85%. A microporous structure with a pore size of 7 μm and a porosity of 12% was made by laser drilling process (power 6 W, scanning rate 20 μm / s) to ensure air permeability. The substrate layer was treated with oxygen plasma with a flow rate of 70 sccm, power of 90 W, and treatment time of 40 s to enhance the adhesion of the humidity response layer.
[0065] 2. Preparation of hydrophilic layer (humidity response layer): Prepare 8wt% PEG aqueous solution with a molecular weight of 8000g / mol. Spin coat the PEG solution on the PC substrate at a speed of 1500rpm for 30s to form a hydrophilic layer (humidity response layer) with a thickness of about 70μm. Dry at 40℃ for 90min, use 2μm PS microspheres as templates, and dope 10wt% to form a microporous structure with a pore size of 1.8μm to improve air permeability.
[0066] 3. Preparation of the middle layer: Using a 9wt% polyacrylonitrile (PAN) solution, the nanofiber membrane was deposited by electrospinning. High-density area: The humidity conduction rate was slow, the voltage was set to 25kV, the spinning rate was 1.0mL / h, the receiving distance was 10cm, and the spinning time was 5min, forming a dense fiber layer. Low-density area: The humidity conduction rate was fast, the voltage was set to 15kV, the spinning rate was 0.5mL / h, the receiving distance was 15cm, and the spinning time was 2min, forming a sparse fiber layer.
[0067] Heat treatment at 70℃ for 1h to increase the interlayer bonding strength.
[0068] 4. Preparation of hydrophobic layer: Use PDMS precursor solution, prepare in a ratio of 10:1, and evenly coat on the PAN layer. Volatilize within 60 minutes to form a nanoporous membrane with a pore size of 200-400 nanometers and a porosity of 25%. Finally, bake at 100°C for 45 minutes to complete the curing of the hydrophobic layer.
[0069] 5. Data test: When the humidity increases from 40% to 80%, the color of the film changes from yellow to red, and the humidity change response time is 2-4s. After 150 humidity cycle tests, the film has no delamination or cracking, showing high durability and stability. The refractive indexes of the 60μm PC base layer and the 70μm PEG hydrophilic layer were measured to be 1.58 and 1.47, respectively, and the optical path difference Δ = 2×(1.58×60+1.47×70) = 395.4μm. The color of the film before color development was yellow (λ≈580), and the interference order = 395.4 / 0.58≈682 can be obtained. The thickness of the hydrophilic layer after moisture absorption is 85μm, the refractive index is 1.51, and the optical path difference Δ = 2×(1.65×50+1.51×100) = 467μm. Then, the interference wavelength after moisture absorption λ = 467 / 682×1000 = 685nm, which is the wavelength of red light.
[0070] Example 3
[0071] 1. Preparation of substrate layer: A porous PET substrate with a thickness of 55 μm was used, the laser power was set to 7 W, the scanning rate was 12 μm / s, the pore size was 3 μm, and the porosity was 18%. Oxygen plasma treatment conditions: gas flow rate 100 sccm, power 75 W, time 50 s, to increase the adhesion of the hydrophilic layer (humidity response layer).
[0072] 2. Preparation of hydrophilic layer (humidity response layer): 6wt% PVA solution (alcoholysis degree of 88%) was used, and 0.5wt% polyacrylamide (PAM) was added to improve humidity responsiveness. The coating rotation speed was 1300rpm, the time was 60s, and a hydrophilic layer (humidity response layer) with a thickness of 90μm was formed. The particle size of PS microspheres was 1.2μm, and the doping amount was 15wt%. After drying, a microporous structure of 1-1.5μm was formed.
[0073] 3. Preparation of the middle layer: The concentration of PAN solution is 11wt%, and the nanofiber layer is deposited on the hydrophilic layer (humidity response layer) by electrospinning. High-density area: The humidity conduction rate is slow, the voltage is set to 25kV, the spinning rate is 1.0mL / h, the receiving distance is 10cm, and the spinning time is 5min, forming a dense fiber layer. Low-density area: The humidity conduction rate is fast, the voltage is set to 15kV, the spinning rate is 0.5mL / h, the receiving distance is 15cm, and the spinning time is 2min, forming a sparse fiber layer. The fiber diameter is 180 nanometers, the porosity reaches 40%, the heat treatment temperature is 80°C, and the time is 2h to ensure the interlayer bonding strength and stability.
[0074] 4. Preparation of hydrophobic layer: PVDF nanoporous membrane was prepared by phase separation method, the solution concentration was 9wt%, and the hydrophobic layer with porosity of 22% and pore size of 300-500nm was formed by cold water phase separation method. It was dried at room temperature for 30min to ensure humidity display stability.
[0075] 5. Data test: When the relative humidity increases from 20% to 90%, the color of the film changes from orange to red, and the change is significant and reversible. The humidity response time is 3s, showing a fast humidity response speed. After 250 humidity cycles, there is no obvious damage to the film structure, and the mechanical stability is excellent. The refractive indexes of the 55μm PET substrate layer and the 90μm PVA hydrophilic layer are measured to be 1.65 and 1.49 respectively, and the optical path difference Δ=2×(1.65×55+1.49×90)=449.7μm. The color of the film before color development is orange (λ≈600), and the interference order can be obtained as 449.7 / 0.6≈750. The thickness of the hydrophilic layer after moisture absorption is 104μm, and the refractive index is 1.53. The optical path difference Δ=2×(1.65×50+1.53×104)=483.24μm, then the interference wavelength after moisture absorption is λ=483.24 / 750×1000=644nm, which is the wavelength of red light.
[0076] The present invention is described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the field without departing from the purpose of the present invention. Many other changes and modifications that do not depart from the concept and scope of the present invention should be regarded as the protection scope of the present invention.
[0077] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0078] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A highly breathable humidity display film based on optical interference, characterized in that: include: A base layer, a humidity responsive layer, an intermediate layer, and a hydrophobic layer; The base layer is made of transparent material; a plurality of air-permeable micropores are arranged on the base layer; the pore size of the micropores is 1-10 μm; and the porosity is 10-20%; The humidity response layer is a thin film layer made of humidity sensitive material with a thickness of 50-100 μm, on which micropores are arranged, and the pore size of the micropores is 0.5-2 μm; to ensure that air and water vapor can freely penetrate the humidity response layer; The middle layer is a nanofiber membrane, wherein the fiber diameter of the nanofiber is controlled to be 100-300nm; the density of the middle layer in the length direction changes in a gradient to control the air permeability of the humidity response layer corresponding to the middle layer of different density; The hydrophobic layer is made of a transparent and breathable material, providing good protection for the humidity display film.
2. The highly breathable humidity display film based on optical interference according to claim 1, characterized in that: The humidity sensitive material is polyethylene glycol or polyvinyl alcohol.
3. A preparation process of a highly breathable humidity display film based on optical interference, characterized in that: The process at least includes the steps of preparing the base layer, specifically: Use polyester or polycarbonate as the base film with a thickness of 30μm-100μm; The base film is processed by laser drilling, the laser power is set to 5-15W, the scanning rate is 10-20μm / s, and micropores with a pore size of 1-10μm and a porosity of 10-20% are prepared; The punched base film is treated with oxygen plasma at a gas flow rate of 50-100 sccm, a power of 50-100 W, and a treatment time of 30-60 s to improve the adhesion of the gradient humidity response layer.
4. The process for preparing a highly breathable humidity display film based on optical interference according to claim 3, characterized in that: The process also includes the step of preparing the humidity response layer, specifically: Prepare a water or ethanol solution of polyethylene glycol or polyvinyl alcohol with a concentration of 5-10wt%; The film is formed by spin coating, the spin coating speed is controlled at 1000-1500 rpm, and the time is set to 30-60 s to obtain a film with a thickness of 50-100 μm; In the film forming process, polystyrene microspheres are added as templates, the particle size of the microspheres is controlled at 0.5-2 μm, and the doping amount is 10-20 wt%; After coating and forming a film, the microsphere template is evaporated to form a microporous structure through a drying treatment at 40-60°C for 1-2 hours.
5. The process for preparing a highly breathable humidity display film based on optical interference according to claim 4, characterized in that: The process also includes the step of preparing the intermediate layer, specifically: Prepare polyacrylonitrile electrospinning solution, the concentration of which is controlled at 8-12wt% to ensure the fluidity and spinning formability of the solution; The area with slow moisture conduction rate was prepared to form a high-density fiber structure, the voltage was set in the range of 20-25 kV, the fiber deposition amount was increased, and the spinning rate was controlled at 1.0 mL / h to generate a dense fiber layer; A low-density fiber structure is formed in the area with faster moisture conduction. The voltage is set at 15-20 kV and the spinning rate is lowered to 0.5 mL / h to form a looser fiber layer, allowing moisture to pass through faster. After electrospinning, the formed PAN fiber membrane was subjected to low temperature heat treatment at 60-80°C for 1-2h.
6. The process for preparing a highly breathable humidity display film based on optical interference according to claim 5, characterized in that: The step of preparing a hydrophobic layer is also included: Preparing a PVDF solution with a concentration of 5-10wt%; Phase separation in a cold water bath forms a PVDF porous membrane with a porosity of 10-30% and a pore size of 100-500nm; Dry at room temperature for 30 min.
Citation Information
Patent Citations
Humidity sensor, manufacturing method thereof and electronic device
CN108593717A
One-way moisture-conducting micro-nano fiber membrane with gradient pore structure and preparation method of one-way moisture-conducting micro-nano fiber membrane
CN114908473A
Breathable film substrate humidity indicator
CN205301182U
Display body
JP2016163955A
Humidity indicator and packaging material
JP2017009551A
Cited By
Heat-shielding breathable tent composite fabric and preparation method thereof
CN121019065A
A heat-shielding and breathable tent composite fabric and a preparation method thereof
CN121019065B